Inhibition of Caspase-3 Provides Neuroprotection for Retina Ganglion Cells againts NMDA-induced Exitotoxicity in Wistar Rats: Oral Presentation - Observational Study - Resident - Maharani; Widyarini, Andriati Nadhilah; Rahmi, Fifin L; Nugroho, Trilaksana; Saubig, Arnila Novitasari; Istiadi, Hermawan (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesGlaucoma is a disorder characterized by the presence of optic neuropathy. Visual impairment inglaucoma is caused by retinal ganglion cell (RGC) apoptosis associated with N-methyl-D-aspartate(NMDA)-mediated excitotoxicity. Excitotoxicity causes an increase in calcium in cells as well asactivation of caspase-3. Glaucoma therapy is currently given to reduce intraocular pressure (IOP),but the damage is still progressing progressively. Hesperidin is known as a neuroprotector that cansuppress calpain overactivation in NMDA-treated retina, thereby reducing the upregulation of TNF-,an inflammatory cytokine, inhibiting calpain activation by suppressing oxidative stress, andattenuating caspase-3 activation. The aim of this study to proving the effect of oral Hesperidin on theexpression of caspase-3 Retinal Ganglion Cell in Wistar rats model of NMDA-induced glaucoma. MethodsExperimental research with post test design only randomized control trial Wistar rats with NMDAinduction were divided into 2 treatment and control groups. The treatment group was given oralHesperidin at a dose of 100mg/kg/day while the control group was given Na-CMC 182 mg/kg/day for3 weeks. Retinal caspase-3 expression was examined by immunohistochemical staining. Data werecollected and processed and then the Mann- Whitney test was performed. (significant p<0.05) ResultsThe mean percentage and intensity of RGC caspase-3 expression in the treatment group were 4.29 ±0.49 it was significantly lower than the control group 6.29 ± 0.95 (p value = 0.003). ConclusionHesperidin provides neuroprotection for RGC againts NMDA- induced exitotoxicity by inhibition ofcaspase-3.